Systematic Literature Review: How Teachers Instill Critical Thinking Character During the Pandemic - Riza Nur Wahyudi; Muhammad Taufik Hidayat (UM Purwokerto Press, 2023)
Critical thinking is an important ability for students in the 21st century. Learners who are less able to think critically will have difficulty when faced with a problem. The purpose of this study is to reveal; 1. What are the learning methods for instilling critical thinking characters in Indonesia during the pandemic, 2.What critical thinking indicators are developed in the learning model, 3.What are the results of the methods used in instilling critical thinking skills. The review method used in this paper is a systematic literature review. The search for articles on the Google scholar uses the help of the Publish or perish application because using the benefit of an application will make it easier to find articles. The selection and screening stages were carried out by analysing the article title, keywords, abstract, background of the problem, author's question, and results and discussion. The results of this study showed that (1) Teachers use varied learning methods during the pandemic, such as e-learning, online class, and blended learning. (2) The critical thinking indicators developed are formulating problems, analysing, concluding, evaluating, building basic skills, providing a further explanation, and managing strategies. (3) The learning methods used during the pandemic can instil students' critical thinking characteristics based on several indicators. However, several learning methods still need help instilling critical thinking skills. The implications of this study are: First, teachers must be skilled in using learning methods with a suitable learning model to instil critical thinking skills in students. This study reveals how teachers instil students' critical thinking skills during the pandemic.